PENGARUH KEBIJAKAN HUTANG TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL MODERASI - DESMON ASA NAINGGOLA, SUBARAMAN (Jurnal Ilmu Manajemen (JIM), 2014)
Abstract : The purpose is to describe the effect of debt policy to firm value with dividend policy as a moderating variable. The first hypothesis is the positive effect of debt policy towards firm value, second the effect of dividend policy on a relationship between debt policy and firm value.The data used are secondary data obtained from the annual reports and financial statements published by each company. Methods used in determining the amount of the sample using purposive sampling method, and then performed classical assumption on the data using Moderated Regression Analysis (MRA) as an analytical instrument.The result showed that debt policy had a negative effect the firm value, but dividend policy can not moderate the relationship between debt policy of firm value. Keywords:debt policy, dividend policy, and firm value.